Generalized equivalence of collections of matrices and common divisors of matrices - Petrychkovych, V.M. (Algebra and Discrete Mathematics, 2004)
The collections (A1, ..., Ak) and (B1, ..., Bk) of matrices over an adequate ring are called generalized equivalent if Ai = UBiVi for some invertible matrices U and Vi , i = 1, ..., k. Some conditions are established under which the finite collection consisting of the matrix and its the divisors is generalized equivalent to the collection of the matrices of the triangular and diagonal forms. By using these forms the common divisors of matrices is described.